Cardiovascular patches applied in congenital cardiac surgery: Current materials and prospects - Mingze Sun; Vincent Reed LaSala; Caroline Giuglaris; David Blitzer; Sophia Jackman; Senay Ustunel; Kavya Rajesh; David Kalfa (Bioengineering & Translational Medicine)
Abstract Congenital Heart Defects (CHDs) are the most common congenital anomalies, affecting between 4 and 75 per 1000 live births. Cardiovascular patches (CVPs) are frequently used as part of the surgical armamentarium to reconstruct cardiovascular structures to correct CHDs in pediatric patients. This review aims to evaluate the history of cardiovascular patches, currently available options, clinical applications, and important features of these patches. Performance and outcomes of different patch materials are assessed to provide reference points for clinicians. The target audience includes clinicians seeking data on clinical performance as they make choices between different patch products, as well as scientists and engineers working to develop patches or synthesize new patch materials.